Pilot study of child-rearing practices among mothers of young children in Dublin - Peskett, C; Roberts, H (Economic & Social Studies, 1972)
Our pilot survey was prompted by an earlier study of infant rearing carried out by John and Elizabeth Newson in Nottingham in 1963, and by a desire to undertake a comparable investigation in Dublin. Work was limited by both time and facilities - but our questionnaire was fairly comprehensive, and we obtained satisfactory cooperation from the mothers we interviewed.
Keywords: Child Rearing; Dublin